Evaluation of Providing Drug Information to Diarrhea Patients at the Bringkoning Community Health Center, Sampang, East Java - Mabruroh Aini Fasa; Naili Uswatun Hasanah; Ach. Faruk Alrosyidi (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2024)
Providing drug information to diarrhea patients is very important and must be taken into account, because accurate, clear and complete information regarding drugs has an impact on the success and achievement of patient therapy. This study aims to determine the Evaluation of Providing drug Information to diarrhea patient at the Bringkoning Sampang Community Health Center based on Minister of Health Regulation No.74 of 2016. This research method uses descriptive with a quantitative approach. The sampling technique uses purposive sampling. The data collection method uses a data cheklist filled in by researchers according to the results of observations. There were 40 diarrhea patients at the Bringkoning Sampang Community Health Center had been implemented but there were still components that had not been conveyed. The components conveyed are the name of the drug, preparation, dosage, how to use it, storage, indications, side effects. The results of the research evaluating the provision of drug information to diarrhea patients were, drug name 100%, drug preparation 75%, dose 100%, how to use 100%, storage 12,55%, indicationts 100%, side effects 100%. Components of drug information that are not conveyed are contraindications, and drug stability.